Validitas Penilaian Keterampilan Berpikir Tingkat Tinggi (HOTS) Tentang Metabolisme - Yosi Laila Rahmi; Ariska Triana Dewi; Rahmawati Darussyamsu (BIOEDUSCIENCE, 2021)
Background: The test results of the higher-order thinking skills assessment instrument of students at several high schools in West Sumatra obtained an average score of 17.88-35.19 which is still low. One way to overcome students' low level of high-order thinking skills is to develop an instrument for assessing higher-order thinking skills. This study aims to produce a valid, practical, and good quality item assessment instrument of students' high order thinking about metabolic material for class XII SMA / MA. Methods: This study uses a 4-D development model. The subjects of this study were 3 validators and 27 students of class XII SMA. The data collection instrument was a validity questionnaire and a practicality test. Results: The data obtained are logical validation with an average percentage of 84.90% valid criteria, empirical validity with a correlation between 0.27-0.54 with valid criteria. Has an average percentage on practical criteria of 86.64%, reliability 0.83 with high categories Conclusions: Instruments for assessing the ability to think at a high level about metabolic material are logically valid and empirically valid, practical, reliable, moderate difficulty level, distinguishing power and good quality options.